Influence of thin-layer soil analogues on the production process of lettuce plants in intensive artificial-light culture - O. R. Udalova; L. M. Anikina; Yu. V. Khomyakov; V. E. Vertebniy; V. I. Dubovitskaya; G. G. Panova (Овощи России)
Relevance.The solution to the problem of providing the population of our country with high - quality plant production all year round is possible when creating high-tech automated phytotechnological complexes based on innovative, resource-saving technologies for growing plants in an artificial climate, including the development of a new generation of root inhabited thin-layer analogues of soils.Materials and methods. The research was carried out under controlled conditions of intensive artificial-light culture, when growing lettuce plants of the Typhoon variety on thin - layer analogs of soil of various composition and a low-volume soil analogue based on high-moor peat with a low degree of decomposition "Agrofit", selected as a reference for comparison, in plant growing light equipment developed at Agrophysical Institute.Results. Evaluation of the influence of thin-film analogues of the soil based on the suspensions Cambrian clay, and /or sapropel in different ratios on the production process of lettuces showed when compared with control (hydrophilic fabric): a positive tendency to increase of height, number of leaves per plant; a significant increase in wet mass by 25-35%, dry mass in 54-80%, percent dry matter in 16-36%; increase of leaf area and photosynthetic capacity at 20-36%, net productivity of photosynthesis by 16-45%; a significant or in a form of tendency to increase in the content of potassium by 14-17%, calcium by 27-35%, zinc by 29-53% and disaccharides by 28-68%. In comparison with the low-volume analogue of the soil based on high-moor peat of a low degree of decomposition "Agrophyte" (standard), it was found an increase in the form of a pronounced positive trend in growth indicators - the height and number of leaves. wet, dry mass of plants, percentage of dry matter; net productivity of photosynthesis, a reliable or in form of trend to increase in leaf area, photosynthetic potential by 20-30%; an increase in the content of mineral elements in lettuce leaves. Possible reasons for the lower productivity of lettuce plants in the control were determined, and it associated with an increase in water intake in leaf tissues against the background of the absence of additional mineral and / or organic nutrition. The content of heavy metals and nitrates did not exceed the maximum permissible concentration (MPC) in all variants. All thin-layer analogs of the soil with the application of suspensions of various compositions can be recommended for growing lettuce in any cultivation facilities in conditions of intensive artificial-light culture.